Life Histories in the Patagonia steppe Rural women, work and collective organization (Huellas, 2015)
This purpose of this paper is to analyze the role of rural women in the organization and creation of collective participation spaces, not only as a way of earning a living that may improve the living conditions of small family farmers but also as a way of resisting the territorial expulsion and the loss of their socio – cultural identity. To achieve this purpose, the paper analyzes a case study: The Steppe Crafts Market, an example of Supportive and Social Economy, which is located in the Pilcaniyeu Department,provinceofRio Negro. The analysis is based on the life-storytelling technique, starting from a thorough interview of one rural craftswoman. The results allow for understanding the way in which women create a working space and a income source that tend to the social reproduction of the household unit, combining production and reproduction and, at the same time, increasing self – esteem, the re-appraisal of their own culture and ancestral knowledge, the motivation for training in the craftsmanship art, in issues related to social and family economy, and in communal participation, among others.
Keywords: rural women; social and supportive economy; Río Negro province